Bhutan: The Unremembered Nation - Chophel, Dendup (Asia Pacific Journal of Anthropology, 2023)

Bhutan: The Unremembered Nation – Vols. 1&2 - Chophel, Dendup (2023)

“Bhutan: The Unremembered Nation” – Vols. 1&2. - Chophel, Dendup (2023)

Buddhism and Modernity: 4th International Vajrayāna Conference An Analytical Conference Report - Chophel, Dendup; Phuntsho, Jigme (Journal of Global Buddhism, 2023)
This article provides an analytical report on the fourth International Vajrayāna Conference themed ‘Buddhism and Modernity’, which was organised by the Centre for Bhutan and GNH Studies in collaboration with Bhutan’s Central Monastic Body.
CRIS-Team Scopus Importer:2023-06-02
Keywords: Bhutan; Buddhism and Modernity; Vajrayāna Buddhism

Buddhism Without Borders: Proceedings of the International Conference on Globalized Buddhism - Chophel, Dendup; Ura, Dasho Karma (The Centre for Bhutan Studies, 2012)

Byis pa’i dpa’ bo: The Dance of Youthful Heroes - Chophel, Dendup; Dorji, Khandu (Bhutanese Buddhism and its Culture, 2014)

Invoking a Warrior Deity: A Preliminary Study of Lo-ju - Chophel, Dendup (Journal of Bhutan Studies, 2011)

Love, hate and tragedy: A three-part history of Bhutan-Cooch relations - Chophel, Dendup; Booth, Julia (2021)

Punctuating “Happiness”: Punctuated equilibrium theory and the agenda-setting of the Gross National Happiness (GNH) policy in Bhutan - Ugyel, Lhawang; Givel, Michael; Chophel, Dendup (Review of Policy Research, 2023)
Gross National Happiness (GNH), a concept first introduced by Bhutan, has gained immense traction as an alternate development paradigm to GDP toward achieving wholesome global progress. In this paper, we investigate the origins of the policy of GNH, through the theoretical lens of the punctuated equilibrium theory (PET), and when and how GNH came to the national agenda. By focusing on the year 2008, that is, when Bhutan's Government transitioned from an absolute monarchy to a democratic constitutional monarchy, this paper analyses the key events that serve as policy windows and the policy entrepreneurs responsible for agenda-setting the policy of GNH. We argue there is a major change, such as, the government changing its form from monarchy to democracy, it is a definitive benchmark as to what punctuation means. In addition to providing a definitive meaning of “punctuation” in public policy, we also identify and discuss the key methodological issues in relation PET and offer explanations through Bhutan's policy of GNH to determine policy punctuation and measuring policy change.
Created from Fastlane, Scopus look-up
Keywords: agenda-setting; Bhutan; GNH (Gross National Happiness); PET (punctuated equilibrium theory); punctuation; well-being

Pursuit of happiness and the impact of Covid-19 on Bhutan’s SDG targets - Chophel, Dendup, Phurba (2021)

The impact and outcomes of (non-education) doctorates: the case of an emerging Bhutan - Maxwell, Tom W.; Chophel, Dendup (Higher Education, 2020)
This is a follow-up study of the impact of education doctorate holders in Bhutan (Maxwell 2018). A representative sample of doctorate holders contributed to this qualitative study. There were anticipated personal outcomes of gains in confidence and self-esteem. There were considerable gains in knowledge and research skills, and mentoring was clearly an important outcome. However, respondents were equivocal about leadership. Workplace conditions appeared to be creating dissatisfaction. Bhutan appears to be close to, or beyond, the cusp where brain drain takes over from brain gain. This, coupled with the under-representation of females amongst doctorate graduates, means development is most likely to be slowed down unless attended to. Ideas for further research are identified.
Created from Fastlane, Scopus look-up
Keywords: Bhutan; Brain drain; Developing country; Doctorate impact; Doctorate outcomes

The life and legacy of Tsangpa Gyare: A three-part series - Chophel, Dendup; Kumagai, Seiji (2022)

The life and legacy of Tsangpa Gyare - Chophel, Dendup; Kumagai, Seiji (2022)

The life and legacy of Tsangpa Gyare - Chophel, Dendup; Kumagai, Seiji (2022)

Visions, Prophecies and Leadership: Oral Accounts of the Life and Death of Terton Drukdra Dorji - Chophel, Dendup; Thinley, Jamtsho; Sangay, Thinley (Journal of Bhutan Studies, 2014)